Speculative States: Citizenship Criteria, Human Rights, and Decolonial Legal Norms in Gerald Vizenor's The Heirs of Columbus. Issue 1 (2016) - Uzendoski, Andrew
Abstract : This essay analyzes Gerald Vizenor's novel The Heirs of Columbus (1991) in terms of human rights law and international legal norms. In this speculative text, Vizenor imagines how Indigenous nations can employ international legal instruments to defend tribal sovereignty and to expand the scope of human rights law to recognize the right to health as a universal human right. Contextualizing the novel alongside both a history of the United Nations' Working Group on Indigenous Populations and a survey of global celebrations of the Columbian quincentennial in 1992, this essay explores the coterminous relationships between Indigenous speculative fiction and international law at the end of the twentieth century.